The present and future of prostate cancer. The importance of physical activity - a comprehensive review of the literature - Kucharski, Tomasz; Gmitrzuk, Julita; Malinka, Zuzanna; Wiśniewska, Katarzyna; Jachymek, Anna; Opatowska, Martyna; Jakubiec, Joanna; Piotrowska, Marta (Quality in Sport, 2024)
Introduction: Prostate cancer is one of the most common malignancies affecting men worldwide, which poses a serious health risk due to its high incidence and impact on quality of life. Despite advances in the diagnosis and treatment of this condition, the management of advanced and aggressive forms of the disease remains complex. Aim of the Study: The aim of this study is to review current diagnostic methods, treatment strategies and prognostic factors in prostate cancer, that a particular focus on personalized medicine and multidisciplinary approaches to improve patient outcomes. Materials and Methods: A comprehensive literature review was conducted using PubMed sources and other scientific databases, focusing on currently available publications. The literature available in the PubMed database was reviewed using the following keywords: “prostate cancer” “prostate cancer diagnosis”, “prostate cancer treatment”, “personalized medicine for prostate cancer”, “physical activity in prostate cancer”. The review included studies on prostate cancer epidemiology, pathogenesis, advances in diagnosis, treatment, physical activity and future research directions. Conclusions: Advances in diagnostic technologies and emerging new therapies have significantly improved the prognosis for patients with prostate cancer. However, continued research and commitment to personalized treatment strategies are essential to meet the challenges of advanced disease. Multidisciplinary collaboration and patient-centered care remain key to optimizing outcomes and improving quality of life for prostate cancer patients.